2020
DOI: 10.1093/gbe/evaa104
|View full text |Cite
|
Sign up to set email alerts
|

Viviparous Reptile Regarded to Have Temperature-Dependent Sex Determination Has Old XY Chromosomes

Abstract: The water skinks Eulamprus tympanum and Eulamprus heatwolei show thermally induced sex determination where elevated temperatures give rise to male offspring. Paradoxically, Eulamprus species reproduce in temperatures of 12–15 °C making them outliers when compared with reptiles that use temperature as a cue for sex determination. Moreover, these two species are among the very few viviparous reptiles reported to have thermally induced sex determination. Thus, we tested whether these skinks possess undetected sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 34 publications
5
73
1
Order By: Relevance
“…We have shown that the gene UBE2H (Ubiquitin Conjugating Enzyme E2 H) is present on the Y chromosome in both B. duperreyi (this study) and the skink E. heatwolei [79]. This strongly suggests that the sex chromosomes of these two skinks share a homologous synteny block and perhaps share homologous sex chromosomes.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We have shown that the gene UBE2H (Ubiquitin Conjugating Enzyme E2 H) is present on the Y chromosome in both B. duperreyi (this study) and the skink E. heatwolei [79]. This strongly suggests that the sex chromosomes of these two skinks share a homologous synteny block and perhaps share homologous sex chromosomes.…”
Section: Discussionsupporting
confidence: 55%
“…One technique, championed by Cortez, et al [78] in exploring variation among mammalian species in the Y chromosome, and recently applied to the Yellow-bellied water skink, Eulamprus heatwolei [79], is to examine read copy number across the genome and identify the half copy number in the XY individuals compared to the XX individuals after screening out repetitive sequence. This technique identifies regions that have been lost from the non-recombining region of the Y chromosome but, remain on the X chromosome, which can be developed as sex specific markers and validated using PCR [79]. Here we used as an alternative complementary approach, in-silico whole genome subtraction to identify male-specific markers in the skink B. duperreyi, subsequently validated them using a PCR panel with known sexes.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the gene UBE2H (Ubiquitin Conjugating Enzyme E2 H) is present on the Y chromosome in both B. duperreyi (this study) and the skink E. heatwolei [79]. This strongly suggests that the sex chromosomes of these two skinks share a homologous syntenic block and perhaps share homologous sex chromosomes.…”
Section: Discussionsupporting
confidence: 55%
“…Two approaches for identifying sex linked markers using whole genome sequencing seem appropriate, both relying on the divergence of the X and Y homologues in the region of recombination suppression. One technique, championed by Cortez, et al [78] in exploring variation among mammalian species in the Y chromosome, and recently applied to the yellow-bellied water skink, Eulamprus heatwolei [79], is to examine read copy number across the genome and identify the half copy number in the XY individuals compared to the XX individuals after screening out repetitive sequence. This technique identi es regions that have been lost from the non-recombining region of the Y chromosome but, remain on the X chromosome, which can be developed as sex speci c markers and validated using PCR [79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation